Twentieth-Century Art : Selection for the Tenth Anniversary of the East Building. (Washington : National Gallery of Art, 1988)
Picasso, Pablo ; Matisse ; Derain ; Modigliani ; Miró ; Gorky ; Smith ; Dubuffet ; Giacometti ; Rothko ; Diebenkorn ; Kelly ; Rauschenberg ; Lichtenstein ; etc.
Twentieth-Century Art : Selection for the Tenth Anniversary of the East Building, National Gallery of Art, Washington, December 13, 1988 - December 31, 1990
Engels
kunstcatalogus